The Prognostic Value of Blood Eosinophil Level in AECOPD is Influenced by Corticosteroid Treatment During Hospitalization - Li J; Liang L; Feng L; Cao S; Cai YS; Li X; Qian Z; Brightling CE; Tong Z (Dove Medical Press, 2023)
Jiachen Li,1 Lirong Liang,1 Lin Feng,1 Siyu Cao,2 Yutong Samuel Cai,3 Xiaobo Li,4 Zhenbei Qian,2 Christopher E Brightling,5 Zhaohui Tong2 1Department of Clinical Epidemiology, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People's Republic of China; 2Department of Respiratory and Critical Care Medicine, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People's Republic of China; 3Centre for Environmental Health and Sustainability, Department of Population Health Sciences, University of Leicester, Leicester, UK; 4Beijing Key Laboratory of Environmental Toxicology, School of Public Health, Capital Medical University, Beijing, People's Republic of China; 5Institute for Lung Health, NIHR Leicester Biomedical Research Centre, University of Leicester, Leicester, UKCorrespondence: Lirong Liang, Department of Clinical Epidemiology, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, No. 8 Gongren Tiyuchang Nanlu, Chaoyang District, Beijing, 100020, People's Republic of China, Tel +86 010-85231547, Email llrcruie@163.comPurpose: Blood eosinophil is a promising biomarker for phenotyping patients with acute exacerbation of COPD (AECOPD). We aimed to evaluate the prognostic value of eosinophil on short- and long-term outcomes stratified by corticosteroid treatment among AECOPD inpatients.Patients and Methods: In this retrospective cohort study, we included patients hospitalized for AECOPD from July 2013 to June 2021 in Beijing, China. Clinical data were collected from electronic medical records. The blood eosinophil count was measured within 24h after admission. Eosinophilic AECOPD was defined as having an eosinophil percentage ≥ 2%. The study outcomes were length of stay (LOS), treatment failure, and AECOPD readmission risk within 3 years of discharge. Multivariable models were used to analyze the associations between blood eosinophil count and outcomes stratified by corticosteroid treatment during hospitalization.Results: A total of 2406 AECOPD patients were included. The median LOS of AECOPD patients was 10 (interquartile range: 8- 14) days. The eosinophil percentage was negatively associated with LOS (P-trend=0.014). Compared with the non-eosinophilic AECOPD group, the eosinophilic group had a 58% lower risk of treatment failure (OR=0.42, 95% CI: 0.20- 0.89) in patients treated with systemic corticosteroids, but no association was observed in those treated with inhaled corticosteroids (ICS) only (OR=0.95, 95% CI: 0.60- 1.52). The eosinophilic group had an increased risk of 90-day re-admission in patients treated with ICS only (HR=1.51, 95% CI: 1.00- 2.29), but not in patients treated with systemic corticosteroids during hospitalization (HR=0.67, 95% CI: 0.39- 1.15). No statistically significant results were found for 180-day, 1-year, or 3-year readmission risk.Conclusion: Elevated blood eosinophils in AECOPD were associated with shorter length of stay and improved response to treatment with systemic corticosteroids, but not inhaled corticosteroids. Our study suggested that a therapeutic approach of using systemic corticosteroid may benefit patients present with eosinophilic AECOPD.Keywords: chronic obstructive pulmonary disease, eosinophilic inflammation, glucocorticoids, interaction